Leveraging the potential of over-the-top platforms in optimizing student learning experience in education - Komal Chopra (Cogent Education)
Over-the-top (OTT) platforms have been considered a popular medium of entertainment. The purpose of the study is to examine how over-the-top platforms can be leveraged in optimizing the student learning experience in education. The research investigated 35 students from 10 different countries having under graduate and postgraduate backgrounds. The research employed a grounded theory approach where a three-level coding process led to the emergence of concepts grounded in the data. The different concepts were identified as analytical learning, group learning, edutainment learning, adaptive learning, and observational learning. A theoretical model for optimizing the learning experience was constructed using the five concepts. The research contributes to the existing literature by highlighting how OTT-based learning can create more adaptive, entertaining, and learner-centered experiences compared to existing learning platforms. The study also provides opportunities for OTT developers to expand in areas of education.